Accurate time dependent wave packet calculations for the N plus OH reaction - Bulut, Niyazi; Roncero, Octavio; Jorfi, Mohamed; Honvault, Pascal (Amer Inst Physics, 2011)
We present accurate quantum calculations of state-to-state cross sections for the N + OH -> NO H reaction performed on the ground 3A '' global adiabatic potential energy surface of Guadagnini et al. [J. Chem. Phys. 102, 774 (1995)]. The OH reagent is initially considered in the rovibrational state upsilon = 0, j = 0 and wave packet calculations have been performed for selected total angular momentum, J = 0, 10, 20, 30, 40, ... ,120. Converged integral state-to-state cross sections are obtained up to a collision energy of 0.5 eV, considering a maximum number of eight helicity components, Omega = 0, ... , 7. Reaction probabilities for J = 0 obtained as a function of collision energy, using the wave packet method, are compared with the recently published time-independent quantum mechanical one. Total reaction cross sections, state-specific rate constants, opacity functions, and product state-resolved integral cross-sections have been obtained by means of the wave packet method for several collision energies and compared with recent quasi-classical trajectory results obtained with the same potential energy surface. The rate constant for OH(upsilon = 0, j = 0) is in good agreement with the previous theoretical values, but in disagreement with the experimental data, except at 300 K. (C) 2011 American Institute of Physics. [doi:10.1063/1.3633240]
Keywords: Statistical-Model; Cross-Sections; Rate Constants; Collisions; Kinetics; N+Oh